Optimalizacija kapaciteta unutarnjeg transporta toplane u Zagrebu - Pašagić, Husein; Radišić, Zdravko; Mandić, Ante (Promet - Traffic&Transportation, 2012)
This paper deals with the methods of establishing the quality-related indices for designing the capacities of the internal circulation system at servicing points of a concrete complex system, i.e. the incineration plant in Zagreb. To obtain the solution to the problem defined the theory of queues has been applied in conjunction with the computer simulation models.